Addressing the stigma of bipolar disorder in Pakistan: A matter of public health importance - Muhammad Ibrahim; Ghaniya Rafi; Abdul Hadi (Journal of the Pakistan Medical Association, 2024)
Madam, Bipolar disorder is a serious psychiatric illness and affects about 2% of the world’s population (1). The disease burden of bipolar disorder is particularly high in low- and middle-income countries (LMICs), where access to adequate mental health care is often limited. It is marked by recurring manic and depressive episodes, profoundly affecting an individual’s mood, energy levels and overall functioning. This condition is linked to elevated rates of morbidity, mortality, disability and social stigma. The undermining of bipolar disorder as a mental illness in Pakistan is a complex issue with a variety of contributing factors. Many people in Pakistan are unaware of this disorder or do not understand its symptoms and impact, which can lead to people with bipolar disorder being stigmatized and discriminated against. Stigmatization of mental illness in the broader context acts as a significant barrier, impeding individuals from actively seeking medical intervention, thereby preventing the timely diagnosis of these conditions. A widely held belief (85%) is that the individual should refrain from disclosing and discussing their condition (2). Moreover, greater negative attitudes were observed towards bipolar disorder and other mental illnesses (higher mean SDS scores) as compared to physical illnesses in Pakistan (3). The stigma often extends to the individual’s family/caretakers and can affect them at numerous levels as well (4). In nations such as Pakistan, the insufficiency of mental health accessibility, particularly in rural locales, constitutes a substantial impediment to individuals seeking assistance for bipolar disorder. The dearth of adequately trained healthcare personnel and suitable facilities represents a primary contributory factor in the underestimation of bipolar disorder as a serious mental health condition. For a group of 3,60,000 people, Pakistan has only 1 psychiatrist (5). Neglecting Bipolar Disorder on national grounds can lead to a significant increment in its related complications as it contributes to higher estimated risks of completed and attempted suicides, migraine, sleep deprivation and increased risk of obstetric complications (6). It is essential to invest in public education for raising awareness and reducing stigma around bipolar disorder. Increasing workforce of mental health practitioners is also vital to lessen population burden. One way to achieve it is to introduce two-year program to ensure feasibility for individuals to pursue a career in psychiatry. Substantial research in this aspect would exponentially improve the lives of people affected with the bipolar disorders and alleviate the burden of bipolar disorder in Pakistan.